Características clínico - epidemiológicas de histoplasmosis diseminada progresiva en pacientes VIH/SIDA atendidos en el Hospital Regional de Loreto, 2022-2024 - Ruíz Torres, Liana Selomit (2025)
This project aims to describe the clinical and epidemiological characteristics of hospitalized patients with HIV/AIDS who present Progressive Disseminated Histoplasmosis, by detecting urinary histoplasma antigen, and to identify the factors associated with this clinical form. The information obtained will be key to improving early diagnosis and adequate management of a disease with high mortality, often underdiagnosed. The study will also allow to differentiate it from tuberculosis and collect clinical and epidemiological data. The objective is to determine the clinical and epidemiological characteristics of Progressive Disseminated Histoplasmosis in patients with HIV/AIDS at the Regional Hospital of Loreto, between 2022 and 2024. The study is observational, analytical, prospective cohort, using a census sample of hospitalized patients. SPSS version 25 will be used for statistical analysis, including Chi-square, Fisher's exact, Student's t and Mann-Whitney U tests. In addition, logistic regression analyses will be performed to evaluate the influence of various factors on the positivity of the urinary Histoplasma antigen, considering a p value<0.05 as statistically significant.